My Fantastic Field Trip : Junior Discovers Saving - Ramsey, Dave.; Hardin, Greg; Trent, John; Yamada, Ken (Brentwood, TN : Ramsey Press, The Lampo Group, Inc., 2015)
Juniors class takes a field trip to see his favorite TV hero, Dollar Bill, who teaches Junior and his friends how to manage their money wisely.
Keywords: School field trips; Juvenile fiction; Children -- Finance, Personal; Juvenile fiction; Saving and investment; Juvenile fiction; Fiction; Juvenile works; Fiction